PENGARUH PARTISIPASI ANGGARAN PADA KINERJA MANAJERIAL PT. BPD BALI CABANG TABANAN: MOTIVASI SEBAGAI VARIABEL PEMODERASI - Anggarini, Ni Nyoman Dewi; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 14 No 1 (2016), 2016)
Purpose of this study was to examine the effect of budgetiparticipation on managerial performance where motivation is used as moderating variables. Data were collected throught questionnaires, interviews, and observations. The first hypothesis tested using simple linear regression analysis techniques and MRA ( Moderated Regression Analysis ) to test the second hypothesis. Research results show that the budgetaryiparticipation has a positive influence on managerial performance. This means that when the budget increased participation also increased managerial performance. The results of the analysis also showed motivation able to moderate the relationship budgetary participation and managerial performance.
Keywords: Budgetary participation, motivation, managerial performance